Schopenhauer and Adorno on Bodily Suffering - Peters, M. author. aut Link
XIII, 279 p.
Keywords: Schopenhauer and Adorno on Bodily Suffering explores how the works of both philosophers revolve around an entwinement of pessimism and optimism, which links statements regarding the wrongness of the world to analyses of the human capability to experience compassion with bodily suffering and to the redeeming qualities of the arts.